(untitled) (Indus Journal of Bioscience Research, 2025)
A study evaluated the growth, carcass characteristics, and meat quality of 12 male Kachhi sheep (3–4 months old) reared under semi-intensive (Group A; n = 6) and intensive (Group B; n = 6) systems for 12 weeks at Sindh Agriculture University, Tandojam. Group A received grazing with supplemental concentrate, while Group B was fed green fodder and concentrate without grazing. Age was determined via dental formula (Schoenian, 2010). Post-slaughter analysis revealed significantly higher (p < 0.05) weight gain (90.37% vs. 50.15%) and dressing percentage (54.56% vs. 51.07%) in Group A. Carcass components, including neck (1.65 vs. 0.97 kg), shoulder (2.37 vs. 1.97 kg), thorax (2.42 vs. 1.83 kg), loin/flank (2.31 vs. 1.45 kg), and legs (2.89 vs. 1.64 kg), were superior in Group A. Conversely, Group B exhibited heavier organ weights: kidneys (0.53 vs. 0.47 kg), liver (0.93 vs. 0.81 kg), spleen (0.31 vs. 0.21 kg), and heart (0.71 vs. 0.62 kg). Meat quality favored Group A, with higher pH (5.95 vs. 5.40), water-holding capacity (63.85% vs. 61.31%), ash (0.86% vs. 0.72%), fat (3.45% vs. 2.65%), moisture (72.73% vs. 70.54%), and protein (21.16% vs. 19.75%). However, Group B had elevated drip loss (4.85% vs. 4.20%) and cooking loss (38.97% vs. 35.19%). The semi-intensive system enhanced carcass yield and meat quality, attributed to grazing’s physiological benefits, despite identical feed quantity/quality. These findings underscore grazing’s critical role in optimizing growth and profitability in Kachhi sheep production, advocating its integration into management strategies.